Teacher Communication Strategies: Fostering Critical Thinking Skills in The Classroom - Sari, Harmita; Samsinar, Samsinar; Rajiman, Widyawanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study seeks to examine educators' communication tactics in instruction to enhance the development of students' critical thinking abilities. This study employs a qualitative methodology utilizing Norman Fairclough's critical discourse analysis paradigm to investigate three primary dimensions: texts, discursive practices, and social practices. Data were gathered from lesson plan documents, transcripts of classroom exchanges, and instructional materials at the secondary school level. The findings indicate that teachers predominantly employ directive and evaluative communication strategies, however there are encouraging signs of incorporating open-ended inquiries and rhetorical techniques that promote elaboration. Nonetheless, these techniques have not been uniformly implemented throughout the research population. Furthermore, the research of discursive practices uncovered conflicts between the requirements of an exam-centric educational framework and the necessity to cultivate students' critical thinking abilities. The study revealed that discourses regarding standardization and the integrative role of education impact learning at the level of social practice. This research significantly enhances the comprehension of communication strategy dynamics in education and provides recommendations for the reform of educational policy and teacher professional development. The findings are pertinent for equipping pupils to navigate the complexities of the modern world by fostering critical thinking abilities.